Lamotrigine誘発性心血管有害事象のハロセン麻酔犬モデルを用いた検討 - 長澤（萩原）, 美帆子; 神林, 隆一; 川合, 眞一; 布井, 啓雄; 廣川, 佳貴; 中瀬古（泉）, 寛子; 武井, 義則; 後藤, 愛; 松本, 明郎; 杉山, 篤 (日本薬理学会年会要旨集, 2021)
Introduction: Lamotrigine, an anti-epileptics or a mood-stabilizer for bipolar disorder, has been known to induce hypotension, elevation of the atrial pacing threshold, cardiac conduction delay, Brugada-like electrocardiographic pattern, wide complex tachycardia and cardiac arrest. We studied what types of electrophysiological changes of lamotrigine may reveal these cardiovascular adverse events.Methods: Lamotrigine was intravenously administered in doses of 0.1, 1 and 10 mg/kg/10 min to halothane-anesthetized dogs (n=4) with monitoring the cardiohemodynamic and electrophysiological variables, possibly providing subtherapeutic to supratherapeutic plasma concentrations.Results: Although the low or middle dose of lamotrigine did not alter any of the variables, the high dose delayed the intra-atrial, atrioventricular nodal and intra-ventricular conductions with the increase of ventricular refractoriness. Conclusion: While lamotrigine by itself may have wide safety margin for hemodynamic variables, its supratherapeutic dose would block Na+ channel in the in situ hearts, partly explaining the clinically reported cardiac adverse events. Lamotrigine might unmask Brugada syndrome in patients having genetic risk factors.